A pipeline approach to single‐particle processing in RELION. Issue 6 (5th June 2017) - Fernandez-Leiro, Rafael; Scheres, Sjors H. W.
Abstract : The formal description of a workflow to cryo‐EM structure determination in the RELION program allows standardization of procedures and on‐the‐fly image processing during data acquisition. Abstract : The formal concept of a workflow to single‐particle analysis of cryo‐electron microscopy (cryo‐EM) images in the RELION program is described. In this approach, the structure‐determination process is considered as a graph, where intermediate results in the form of images or metadata are the vertices, and different functionalities of the program are the edges. The new implementation automatically logs all user actions, facilitates file management and disk cleaning, and allows convenient browsing of the history of a project. Moreover, new functionality to iteratively execute consecutive jobs allows on‐the‐fly image processing, which will lead to more efficient data acquisition by providing faster feedback on data quality. The possibility of exchanging data‐processing procedures among users will contribute to the development of standardized image‐processing procedures, and hence increase accessibility for new users in this rapidly expanding field.